A Combined Chronic Low-Dose Soluble Epoxide Hydrolase and Acetylcholinesterase Pharmacological Inhibition Promotes Memory Reinstatement in Alzheimer's Disease Mice Models - Júlia Jarne-Ferrer; Christian Griñán-Ferré; Aina Bellver-Sanchis; Santiago Vázquez; Diego Muñoz-Torrero; Mercè Pallàs (MDPI AG, 2022)
Alzheimer's disease (AD) is a progressive neurological disorder with multifactorial and heterogeneous causes. AD involves several etiopathogenic mechanisms such as aberrant protein accumulation, neurotransmitter deficits, synaptic dysfunction and neuroinflammation, which lead to cognitive decline. Unfortunately, the currently available anti-AD drugs only alleviate the symptoms temporarily and provide a limited therapeutic effect. Thus, new therapeutic strategies, including multitarget approaches, are urgently needed. It has been demonstrated that a co-treatment of acetylcholinesterase (AChE) inhibitor with other neuroprotective agents has beneficial effects on cognition. Here, we have assessed the neuroprotective effects of chronic dual treatment with a soluble epoxide hydrolase (sEH) inhibitor (TPPU) and an AChE inhibitor (6-chlorotacrine or rivastigmine) in in vivo studies. Interestingly, we have found beneficial effects after chronic low-dose co-treatment with TPPU and 6-chlorotacrine in the senescence-accelerated mouse prone 8 (SAMP8) mouse model as well as with TPPU and rivastigmine co-treatment in the 5XFAD mouse model, in comparison with the corresponding monotherapy treatments. In the SAMP8 model, no substantial improvements in synaptic plasticity markers were found, but the co-treatment of TPPU and 6-chlorotacrine led to a significantly reduced gene expression of neuroinflammatory markers, such as interleukin 6 (Il-6), triggering receptor expressed on myeloid cell 2 (Trem2) and glial fibrillary acidic protein (Gfap). In 5XFAD mice, chronic low-dose co-treatment of TPPU and rivastigmine led to enhanced protein levels of synaptic plasticity markers, such as the phospho-cAMP response element-binding protein (p-CREB) ratio, brain-derived neurotrophic factor (BDNF) and postsynaptic density protein 95 (PSD95), and also to a reduction in neuroinflammatory gene expression. Collectively, these results support the neuroprotectant role of chronic low-dose co-treatment strategy with sEH and AChE inhibitors in AD mouse models, opening new avenues for effective AD treatment.